(untitled) (Praxis Educativa, 2022)
Given the importance of teachers in the development of educational inclusion, a study was conducted to determine whether there exists any relationship between inclusive self-ascription and empathy in Chilean teachers. The study considered 556 teachers from public and subsidized-private secondary education schools, with and without integration project. It used a non-experimental, cross-sectional, descriptive-correlational design; data was collected by using and the Cambridge Depersonalization Scale (Baron-Cohen, 2004) and the Booth and Ainscow´s Inclusive Self-ascription Scale (2011). The results indicate that there is a weak relationship between the variables self-ascription and empathy, without differences between secondary school teachers from public schools with and without integration project. It is concluded that even when at a theoretical level there exists certain link between positive attitudes towards others and social inclusion (Avramidis and Norwich, 2004; Subirats, Alfama and Obradors, 2009), it was not possible to support empirically what these authors propose in their theory.